Eksternalitas dan Biaya Eksternal karena Pencemaran Pertanian - Joko Mariyono (Jurnal Dinamika Sosial Ekonomi, 2002)
Agriculture the significant sector supporting the economy of development countries. The sector has experienced rapid growth the new technology called green revolution was introduced. Implementing the technology agricultural production particularly food crops can be doubled. Enhancing production was conducted by cultivating high yields varieties that highly supported by using chemical input such fertilizers and pesticides. But, however such method of production has caused further problem, namely enviromental deprivation, since the chemical inputs have negative externality.  The value  of enviromental damaged is considerably high, mainly associated by unwise chemical input use. In many countries have performed valuation toward the externalities in monetary term as external cost. the approach of valuaction varies from one country to other counties. It depends on the type of externalities. Efforts to  reduce the externalities is being tried in order to save the environment of the only one of the earth.Key words : externality, external cost, enviromental deprivation